Characterization of the Nrt2.6 gene in Arabidopsis thaliana: a link with plant response to biotic and abiotic stress. - Julie Dechorgnat (Public Library of Science (PLoS), 2012)
The high affinity nitrate transport system in Arabidopsis thaliana involves one gene and potentially seven genes from the NRT1 and NRT2 family, respectively. Among them, NRT2.1, NRT2.2, NRT2.4 and NRT2.7 proteins have been shown to transport nitrate and are localized on the plasmalemma or the tonoplast membranes. NRT2.1, NRT2.2 and NRT2.4 play a role in nitrate uptake from soil solution by root cells while NRT2.7 is responsible for nitrate loading in the seed vacuole. We have undertaken the functional characterization of a third member of the family, the NRT2.6 gene. NRT2.6 was weakly expressed in most plant organs and its expression was higher in vegetative organs than in reproductive organs. Contrary to other NRT2 members, NRT2.6 expression was not induced by limiting but rather by high nitrogen levels, and no nitrate-related phenotype was found in the nrt2.6-1 mutant. Consistently, the over-expression of the gene failed to complement the nitrate uptake defect of an nrt2.1-nrt2.2 double mutant. The NRT2.6 expression is induced after inoculation of Arabidopsis thaliana by the phytopathogenic bacterium Erwinia amylovora. Interestingly, plants with a decreased NRT2.6 expression showed a lower tolerance to pathogen attack. A correlation was found between NRT2.6 expression and ROS species accumulation in response to infection by E. amylovora and treatment with the redox-active herbicide methyl viologen, suggesting a probable link between NRT2.6 activity and the production of ROS in response to biotic and abiotic stress.